(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the role of technology in teaching English as a foreign language. It focuses on digital transformation in education, the pedagogical impact of technological tools, and their influence on learner autonomy, motivation, communicative competence, and classroom interaction. The study also addresses challenges such as digital inequality, teacher preparedness, and classroom management in technology-enhanced learning environments..